Le conseil communautaire de Notre Dame de Grâce règlements généraux - NDG Community Council (NDGCC) (2019)

Notre Dame de Grâce : Community Council By-Laws - NDG Community Council (NDGCC) (2019)

Notre Dame de Grâce carte ressource - NDG Community Council (NDGCC) (2019)

Annual Report : 2018-2019 - NDG Community Council (NDGCC) (2019)

Rapport annuel : 2018-2019 - NDG Community Council (NDGCC) (2019)

Report on the 2019 NDG Community Health Forum - NDG Community Council (NDGCC) (2019)
On October 20th 2019, the NDG Senior Citizens’ Council sponsored a community health forum organized in collaboration with the NDG Working Group on Health and the NDG Community Council. The African-Canadian Development and Prevention Network (ACDPN), Hear Entendre Quebec and Prevention NDG were also engaged regularly throughout the process in order to address issues of access and cultural sensitivity in the discussions. The goal of the forum was to inform the residents of NDG and surrounding areas about the resources that exist through institutions supported by the Centre Intégré Universitaire de Santé et de Services Sociaux for the Center-West of Montreal (Hereafter CIUSSS-CODIM), as well as many of the local community organizations, in particular as they relate to health and health access. Further, the event aimed to create a discourse between the health and social service providers, encouraging participants to open a dialogue regarding the gaps in services experienced by residents so that the Working Group on Health could be better informed for future action.